Wide Rayleigh waves bandgap engineered metabarriers for ground born vibration attenuation. (1st November 2021) - Muhammad; Lim, C.W.; Kamil Żur, Krzysztof
Graphical abstract: Highlights: A novel engineered metabarriers are proposed for seismic shielding purposes. Analytical model is developed for modal analysis and resonant modes identification. 3D FEM simulations are performed to investigate the Rayleigh wave attenuation. The seismic metawedges phenomena are discussed for proposed metabarriers. Implementing actual earthquake record real time performance of bandgap is validated. Abstract: The present study proposes two types of engineered resonant metabarrier designs for ground born vibration attenuation at subwavelength frequency region. By establishing analytical and full-scale 3D numerical models, the effectiveness of metabarrier in attenuating incoming Rayleigh surface waves in the earthquake frequency range of interest is investigated. The metabarrier designs are comprised of a cylindrical steel mass encapsulated inside a hollow concrete setup mounted with low-stiffness rubber bearings. The interaction of surface ground motion caused by the propagation of Rayleigh waves with the vertical resonant mode of metabarriers result in the trapping and/or mode conversion of Rayleigh waves into bulk shear waves that propagate deep into the ground. This so-called wave hybridization or the local resonance phenomena induces an extremely wide low frequency bandgap from both designs that is found effective in attenuating incoming Rayleigh waves at the deep-subwavelength scale. By varying the height and arrangement types of resonant metabarriers, the seismic metawedge phenomena are also investigated. In the bandgap frequency range, the Rayleigh waves attenuation is validated by performing a full-scale 3D numerical frequency response analysis including an actual earthquake record (Imperial Valle-1940 El-Centro) based time history analysis. The findings reported indicate such metabarriers can be embedded into the ground surrounding civil infrastructures to be protected from earthquake hazards.